1996
DOI: 10.1093/oxfordjournals.humrep.a019294
|View full text |Cite
|
Sign up to set email alerts
|

Improved fertilization and implantation rates after non-touch zona pellucida microdrilling of mouse oocytes with a 1.48  m diode laser beam

Abstract: The safety of microdrilling the zona pellucida of mouse oocytes with a 1.48 microm diode laser has been investigated by determining the ability of mouse oocytes to fertilize in vitro and develop in vivo. Mice born after transfer of control and zona pellucida-microdrilled embryos into foster mothers were submitted to anatomical and immunohistochemical investigations, and their aptitude to breed was assessed in two subsequent generations. Decoronization of the oocytes with hyaluronidase induced a reduction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…Mouse Oocytes and Zygotes-6 to 9-week-old IB1/JIP-1 heterozygous females were stimulated (day 1) with one peritoneal injection (10 IU/0.2ml) of follicle-stimulating hormone (Folligon; Intervet AG, Pfä ffikon, Switzerland) followed on day 3 by a second injection (10 IU/0.2ml) of hCG (Pregnyl; Organon, Zü rich, Switzerland) to induce ovulation (26). For the recovery of oocytes, females were killed 13 h after hCG administration by cervical dislocation.…”
Section: Generationmentioning
confidence: 99%
“…Mouse Oocytes and Zygotes-6 to 9-week-old IB1/JIP-1 heterozygous females were stimulated (day 1) with one peritoneal injection (10 IU/0.2ml) of follicle-stimulating hormone (Folligon; Intervet AG, Pfä ffikon, Switzerland) followed on day 3 by a second injection (10 IU/0.2ml) of hCG (Pregnyl; Organon, Zü rich, Switzerland) to induce ovulation (26). For the recovery of oocytes, females were killed 13 h after hCG administration by cervical dislocation.…”
Section: Generationmentioning
confidence: 99%
“…As laser beams may now be guided through optical lenses, it is possible to exactly focus the laser beam to less than 1 Ìm in diameter. In assisted reproductive technologies, laser light was used for manipulation of sperm and oocytes, thus supporting or replacing conventional manipulation methods [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure seems to be safe, as drilled mouse embryos give rise to normal and fertile offspring. Pups derived from zona pellucida microdrilled embryos were comparable with those obtained from control embryos, confirming the lack of deleterious effects from the laser treatment [Germond et al, 1996]. It is concluded that the technology may be investigated in humans, particularly when the zona pellucida represents the main impediment to fertilization or assisted hatching, but clinical studies have not been reported so far.…”
Section: Animal Studies and In Vitro Human Embryo Hatchingmentioning
confidence: 60%
“…However, infrared radiation is the most appropriate, especially when mutagenic risks are taken into account. The 1.48-Ìm diode laser allows rapid, precise and easily controlled lysis of the zona pellucida [Rink et al, 1994;Germond et al, 1995Germond et al, , 1996. Zona opening is performed by exposing the zona pellucida to laser light.…”
Section: Different Techniques For Assisted Hatchingmentioning
confidence: 99%